(untitled) (Global Journals of Research in Engineering, 2014)
In pursuit of improving the safety of automobile many companies have invested in developing various systems Engine Immobiliser is one such innovation Eventually the RFID based Engine Immobiliser is becoming prone to getting hacked which compromises the very purpose of the device Ethical hacker Karsten Nohl of Security Research Labs was able to crack the Hitag 2 car immobiliser algorithm used by Dutch firm NXP Semiconductors in around six hours The need of the hour is to design an infallible system which enhances the security of the vehicle We propose a system with a Face Recognition System which replaces the RFID based system Additionally a Passive Defense System PDS is also implemented that further reduces the chances of vehicle theft The system also has a Driving Assistant Module DAM to help the driver drive in reduced visibility conditions like torrential rainfall dense fog and the like Another addition is the alcohol detection which is useful in avoiding drunken driving